Pemanfaatan Media Sosial dalam Penguatan Daya Saing Destinasi Pariwisata Berkelanjutan: Studi Kualitatif di Desa Wisata Tetebatu, Lombok Timur - Natila Rizka Safitri; Mufidah; Rohani Inta Dewi; Hapipi Jayadi; Riri Ardika Cahyani Paradita (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
TThis study aims to analyze the use of social media in strengthening the competitiveness of sustainable tourism destinations in Tetebatu Tourism Village, East Lombok. In the context of tourism digitalization, social media functions not only as a promotional tool but also as a medium for destination image building, tourist interaction, and the involvement of local actors in tourism management processes. This study employed a qualitative approach with a descriptive-analytical design to obtain an in-depth understanding of social media utilization at the local destination level. Data were collected through field observations and in-depth interviews with destination managers, village officials, tourism actors, and tourists, and were supported by documentation studies. The results indicate that social media contributes to expanding the reach of destination information, strengthening Tetebatu’s image as a nature- and community-based tourism destination, and encouraging active participation from local communities. However, the strengthening of destination competitiveness remains contextual and is influenced by management capacity, consistency in content creation, and the integration of social media strategies into sustainable tourism governance frameworks